Factors influencing asset misappropriation in financial institutions: The application of fraud diamond theory - Hanum Md Isa, Farah; Alias, Norhayati; Mohd Ali, Mazurina; Hasniza Haron, Noor; Bi Mohamed Sadique, Raziah; Johan, Noraini (Edelweiss Applied Science and Technology, 2024)
Fraud cases in financial institutions have increased globally in recent years and Malaysia is no exception. Internal actors committed the most frauds, causing 69% of organisations to suffer from their actions, as compared to only 17% organisations dealing with frauds caused by external actors. Moving towards the future, a greatest concern of fraud in Malaysia revolves around asset misappropriations. It is necessary to understand why people commit fraud to reduce the number of asset misappropriation occurrences. Thus, the research aims to investigate factors influencing asset misappropriation in financial institutions. The research suggested elements in the Fraud Diamond Theory as influencing factors, namely pressure, opportunity, rationalization, and capability. Data for the research was obtained from a survey questionnaire that polled public attitudes with regards to the selected factors influencing asset misappropriation occurrences. 111 respondents participated in the survey, for which the findings showed that only pressure and capability had a significant relationship with asset misappropriation. Opportunity and rationalisation were found to have no significant relationship with asset misappropriation. This implies that personal integrity is a more critical issue, as compared to rationalisation. The research is hoped to help financial institutions by assisting banking and financial sectors, as well as policymakers in managing risks of fraud and developing policies to reduce operational risk.